Effect of rootstocks on growth, yield, fruit quality and leaf nutrients of Khasi mandarin (Citrus reticulata) - TALANG, HAMMYLLIENDE; JHA, A K; RYMBAI, H; ANGAMI, T; DEVI, M B; VANLALRUATI; ASSUMI, S R; THAKUR , A; CHOUDHURI, B U (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2023 and 2024 at ICAR-Research Complex for NEH Region, Umiam, Meghalaya to examine the influence of seven rootstocks comprising Citrus karna Raf, Poncirus trifoliate (L.) Raf., Citrus jambhiri Lush., Citrus limonia (L.) Osb., Citrus latipes (Swingle) Yu. Tanaka, Citrus taiwanica (Tan. & Shim.) and Citrus volkameriana (Ten. & Pasq.) on the growth, yield, fruit quality and leaf mineral composition of Khasi mandarin (Citrus reticulata). Results indicated significant difference in growth parameters, with Citrus jambhiri Lush. showing superior plant height, trunk girth and canopy spread as compared to other rootstocks. With regards to the yield parameters, Khasi mandarin plants grafted on Citrus limonia (L.) Osb. recorded maximum yield, fruit size, number of segments and juice content whereas number of fruits per tree and fruit weight were highest with Citrus jambhiri Lush and Citrus volkameriana (Ten. & Pasq.), respectively. Biochemical traits of the fruits were showing superiority in Citrus volkameriana (Ten. & Pasq.). The rootstocks also imparted significant influence on the leaf nutrient contents. Plants on Citrus jambhiri Lush had the highest level of leaf nitrogen, phosphorus, potassium, calcium, and iron, while those on Citrus limonia (L) Osb. had the highest levels of magnesium, zinc, and copper. Based on the overall performance in growth, yield, fruit quality and nutrient accumulation patterns, Citrus jambhiri Lush., Citrus limonia (L) Osb. and Citrus volkameriana (Ten. & Pasq.) can be recommended as suitable rootstocks for the Khasi mandarin.